2008
DOI: 10.1088/0022-3727/41/5/055501
|View full text |Cite
|
Sign up to set email alerts
|

The backscattering factor for systems with a buried layer

Abstract: The accuracy of quantitative Auger-electron spectroscopy analysis can be further improved, for example, by a proper description of the matrix effects. The backscattering effect in Auger spectrometry for a uniform medium has attracted significant interest in the literature. Studies on the Auger backscattering factor (BF) for a layered sample are unique, and the case of the BF for a buried layer in a certain material is still untouched. We develop the Monte Carlo model for the BF calculation for a layered system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In the case of such studies, the primary electron beam excites several layers and the BF is to be calculated for such a complex system. Zommer and Jablonski developed a Monte Carlo (MC) model for calculations of the BF for multilayered systems [16]. We will show that MC based calculation of the BF can describe the experimental findings.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…In the case of such studies, the primary electron beam excites several layers and the BF is to be calculated for such a complex system. Zommer and Jablonski developed a Monte Carlo (MC) model for calculations of the BF for multilayered systems [16]. We will show that MC based calculation of the BF can describe the experimental findings.…”
Section: Introductionmentioning
confidence: 93%
“…The MC model for BF calculations for a buried layer in a multilayered system has been developed in [16] and the formula derived there enabling the calculations of BF is…”
Section: Calculation Of Auger Intensitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Zommer and coworkers developed a theoretical model including simultaneously two effects: elastic scattering of Auger electrons and backscattering of the primary beam electrons. Monte Carlo (MC) simulations of both phenomena, performed for the Ni/C multilayer deposited on Si, indicated that the shape of the in‐depth AES profile is slightly different for each layer, even if identical thicknesses of analyzed layers have been assumed.…”
Section: Introductionmentioning
confidence: 99%